Ultrasound-homogenization-assisted extraction of polyphenols from coconut mesocarp: Optimization study - Jing Yang; Nana Li; Chunyu Wang; Tao Chang; Huichuan Jiang (Ultrasonics Sonochemistry, 2021)
Coconut pericarp (shell fiber (mesocarp) and shell (endocarp)), the main by-product of coconut production, is often discarded and causing serious environmental pollution. To make better use of coconut pericarp, the extraction process of polyphenols from coconut mesocarp (CM) carefully studied by screening seven solvent systems, optimizing the assisted ultrasonic process by response surface methodology, and comparing the four processes of Ultrasound-Assisted Extraction (UAE), Homogenization-Assisted Extraction (HAE), Homogenization-Ultrasound-Assisted Extraction (HUAE), and Ultrasound-Homogenization-Assisted Extraction (UHAE). The UAE and HAE are considered to be the main methods for efficient extraction of natural active ingredients. The former effectively destroys the cell wall structure and promotes the intermolecular diffusion based on the cavitation, thermal and mechanical effect of ultrasonic, while the latter breaks the material based on strong shear force between the rotor and stator. Their combinations (HUAE and UHAE) enhance the damage to the cell wall of raw materials and improve the extraction efficiency by the synergistic effect. The results showed that using 60% acetone (V : V) as extraction solvent, solid-liquid ratio of 1:5 g mL−1, ultrasonic temperature of 80 ℃, ultrasonic time of 80 min, ultrasonic power of 225 W, and then homogenizing at 10,000 rpm for 10 min, the total flavonoid content of CM reached the maximum value of 551.99 ± 12.69 mg Rutin g−1 dry weight (dw), while the total phenolic content reached the maximum value of 289.48 ± 4.41 mg GAE g−1 dw at 10,000 rpm for 5 min, which may be related to the oxidative degradation of polyphenols caused by the increase of polyphenol oxidase with the extension of homogenization time. This study provides a technical guarantee for the further utilization of phenolic substances in CM.